Prediction of Behavioral Patterns of Number Students Using Artificial Neural Networks. - Endah Nurjanah; Dyah Nur Rochmah; Bagus Wirawan (Mulia International Journal in Science and Technical, 2018)
This study aims to predict student behavior patterns so they can predict based on the number of students. To achieve optimal results, this study uses Artificial Neural Networks with the Backpropagation method. A case study was conducted at the Faculty of Computer Science, X University. The data used is data on the number of students in the academic year two years ago as training data and the school year data is two years after that as testing data. Furthermore, the data are analyzed with several network architecture patterns, and the best design will be chosen to be implemented into the Matlab program. The system results show a correlation between the number of students that occur.